Analysis of spray particles entrance of Right-angle cold spray nozzle based on CFD - Kun Tan (Mechanics and Advanced Technologies, 2023)
Cold spray technology is a solid-state deposition technology, and the nozzle is an important part of the cold spray system. This article proposes a right-angle nozzle. The characteristic of this nozzle is that it can change the flow direction of the gas flow inside the nozzle to realize spraying on the surface of special parts; the acceleration of particles by the right-angle nozzle with different particle entrances is studied. The results show that the outlet center velocity of the right-angle nozzle with a circular throat section is greater, the viscous boundary layer effect is better, and the effective circulation area is larger; the maximum airflow velocity near the outlet of the right-angle nozzle at the particle entrance A is 663.4m/s; it can also effectively avoid the deposition of particles inside the right-angle nozzle, thereby reducing the loss of kinetic energy during the acceleration of particles in the right-angle nozzle; the research on the structure of the new right-angle cold spray nozzle can provide reference for the nozzle of cold spray technology Opinion.